Effective promotion of oxygen reduction activity by rare earth doping in simple perovskite cathodes for intermediate-temperature solid oxide fuel cells - Zhang, Wenwen; Zhang, Lifang; Guan, Kai; Zhang, Xiong; Meng, Junling; Wang, Haocong; Liu, Xiaojuan; Meng, Jian (Journal of power sources, 2020)
The development of highly efficient cathode materials at intermediate temperatures is critical to realize the large-scale commercialization of solid oxide fuel cells (SOFCs). Here, a facile way is presented to tune both the crystal structure and the electrochemical performance of simple perovskite oxides as cathode materials by doping rare earth cations (La, Pr, Nd) in A site. The obtained cubic perovskites LnxBa1−xCo0.7Fe0.3O3−δ (Ln = La, Pr, Nd, x = 0.1, 0.2) exhibit enhanced electrocatalytic activity in comparison with their parent compound BaCo0.7Fe0.3O3−δ, with Pr0.1Ba0.9Co0.7Fe0.3O3−δ reaching area specific resistance of 0.038 and 0.026 Ω cm2 and peak power densities of 905.9 and 1236.4 mW cm−2 at 650 and 700 °C, respectively. Such enhancement is a result of the stabilized cubic structure and the promoted oxygen vacancy formation and oxygen adsorption-dissociation process due to rare-earth doping (Pr is more effective for its redox-active character) by the combination of experimental characterization and first-principles calculation. Furthermore, Pr-doped materials also maintain favorable durability at 600 °C (800 mA cm−2 for ~150 h). These findings in this work may provide new insights into the design of cathode materials for other perovskite systems in SOFCs, especially those involving rare earths. [Display omitted] •The effect of rare earth doping on BCF cathodes is systematically investigated.•Rare earth doping can effectively stabilize the cubic phase of BCF.•Pr doping significantly enhances the oxygen reduction activity of BCF.